Analisis Pengetahuan dan Tingkat Kepatuhan Wajib Pajak Pengusaha Marketplace di Kalangan Generasi Z - Fatmanah, Yiska; Arasy Harwida, Gita (LPPM POLITEKNIK LP3I BANDUNG, 2024)
The purpose of this research is to analyze the knowledge and level of tax compliance of marketplace entrepreneurs in Generation Z. Researchers use qualitative methods with an interpretive paradigm. Data collection was carried out through interviews by exploring the perspectives of four Generation Z people, who are individual MSME taxpayers, have been marketplace entrepreneurs for at least 2 years, and have a turnover of under IDR 500 million per year. The research results showed that in the sample studied, no one knew about the tax obligations for the online business they ran. Even though they were only required to report taxes without paying, none of the research subjects fulfilled their obligations. The reasons for this behavior vary, starting from the perception that the tax reporting process is complicated and burdensome. busy running an online business. The view that online businesses do not experience direct benefits from tax contributions like offline businesses. Changes regarding tax regulations for online businesses and the behavior of non-compliant co-workers also influence their non-compliance. The suggestion for the marketplace is to require every seller to deposit proof of tax report every year. Meanwhile, the suggestion for the government is to provide tax education to MSME business actors who operate online.